Prospects for accurate distance measurements of pulsars with the Square Kilometre Array: Enabling fundamental physics - Smits, R.; Tingay, Steven; Wex, N.; Kramer, M.; Stappers, B. (EDP Sciences, 2011)
Parallax measurements of pulsars allow for accurate measurements of the interstellar electron density and contribute to accurate testsof general relativity using binary systems. The Square Kilometre Array (SKA) will be an ideal instrument for measuring the parallaxof pulsars, because it has a very high sensitivity, as well as baselines extending up to several thousands of kilometres. We performedsimulations to estimate the number of pulsars for which the parallax can be measured with the SKA and the distance to which aparallax can be measured. We compare two different methods. The first method measures the parallax directly by utilising the longbaselines of the SKA to form high angular resolution images. The second method uses the arrival times of the radio signals of pulsarsto fit a transformation between time coordinates in the terrestrial frame and the comoving pulsar frame directly yielding the parallax.We find that with the first method a parallax with an accuracy of 20% or less can be measured up to a maximum distance of 13 kpc,which would include 9000 pulsars. By timing pulsars with the most stable arrival times for the radio emission, parallaxes can be measured for about 3600 ms pulsars up to a distance of 9 kpc with an accuracy of 20%.